Small RNA Functions as a Trafficking Effector in Plant Immunity - Zhu, Chen (Int J Mol Sci, 2019)
Small RNAs represent a class of small but powerful agents that regulate development and abiotic and biotic stress responses during plant adaptation to a constantly challenging environment. Previous findings have revealed the important roles of small RNAs in diverse cellular processes. The recent discovery of bidirectional trafficking of small RNAs between different kingdoms has raised many interesting questions. The subsequent demonstration of exosome-mediated small RNA export provided a possible tool for further investigating how plants use small RNAs as a weapon during the arms race between plant hosts and pathogens. This review will focus on discussing the roles of small RNAs in plant immunity in terms of three aspects: the biogenesis of extracellular small RNAs and the transportation and trafficking small RNA-mediated gene silencing in pathogens.